Comparison of intravenous and non-intravenous antibiotic regimens in eradication of P. aeruginosa and MRSA in cystic fibrosis - KARAHASAN, AYŞEGÜL; ERDEM ERALP, ELA; GÖKDEMİR, YASEMİN (WILEY, 2021)
Background Chronic pulmonary infection is the leading cause of mortality and morbidity in patients with cystic fibrosis (CF). The most common pathogens isolated in CF are Staphylococcus aureus (SA) and Pseudomonas aeruginosa (PA). Chronic infection of PA and methicillin-resistant S. aureus (MRSA) are associated with worse survival and antibiotic eradication treatment is recommended for both. This study compared the outcomes between intravenous (IV) and non-IV antibiotics in eradication of PA and MRSA. Methods This was a single-center retrospective study. All respiratory specimen cultures of 309 CF patients and eradication regimens between 2015 and 2019 were reviewed. Patients received eradication treatment in case of first ever isolation or new isolation after being infection-free >= 1 year. The primary analysis was the comparison of the percentage of successful eradication after receiving IV and non-IV eradication regimens. Demographic and clinical risk factors for eradication failure were also analyzed. Results One hundred and two patients with PA isolations and 48 patients with MRSA were analyzed. At 1 year, 21.6% in PA group and 35.4% in MRSA group were successfully eradicated. There was not any statistically significant difference between IV versus non-IV antibiotic regimens on eradication in either group. Additionally, none of the clinical risk factors was significantly associated with eradication failure in PA and MRSA groups. Conclusion In the eradication of PA and MRSA, IV and non-IV treatment regimens did not show any superiority to one another. Non-parenteral eradication could be a better option considering the cost-effectiveness and the treatment burden of IV treatments due to hospitalization and the need for IV access.
Keywords: antibiotic; chronic infection; cystic fibrosis; eradication; MRSA; Pseudomonas aeruginosa; RESISTANT STAPHYLOCOCCUS-AUREUS; QUALITY-OF-LIFE; PSEUDOMONAS-AERUGINOSA; SINGLE-CENTER; FEV1 DECLINE; INFECTION; CHILDREN; INFLAMMATION; GUIDELINES; THERAPY